2009
DOI: 10.1111/j.1365-2265.2009.03531.x
|View full text |Cite
|
Sign up to set email alerts
|

IGF system in children with congenital disorders of glycosylation

Abstract: Inadequate glycosylation of IGFBP-3 and ALS has a negative effect on the function of these proteins in vivo. This study provides the first evidence in humans for the importance of glycosylation on components of the IGF system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 27 publications
6
45
0
Order By: Relevance
“…Levels of (non-glycosylated) IGF-1, IGF-BP3 and ALS were also found to be reduced in other CDG patients, contributing to their poor linear growth. 1,4 Decreased transferrin galactosylation on mass spectrometry is a typical finding in patients with PGM1 deficiency. During in vitro studies with patient fibroblasts, improved glycosylation was demonstrated with galactose supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of (non-glycosylated) IGF-1, IGF-BP3 and ALS were also found to be reduced in other CDG patients, contributing to their poor linear growth. 1,4 Decreased transferrin galactosylation on mass spectrometry is a typical finding in patients with PGM1 deficiency. During in vitro studies with patient fibroblasts, improved glycosylation was demonstrated with galactose supplements.…”
Section: Discussionmentioning
confidence: 99%
“…However, levels of insulin-like growth factor 1 (IGF-1) and IGF-binding protein 3 were low, as they are in patients with CDG-Ib, a glycosylation disorder in which dietary supplementation with mannose improves glycosylation and growth. 3,25 A detailed discussion of the literature concerning the role of glycosylation in the gonadotropin and IGF-1 systems is provided in the Supplementary Appendix.…”
Section: Discussionmentioning
confidence: 99%
“…To the contrary, we did not observe any N-glycosylation site in all mammalian IGFBP-2. However, the N-glycosylation had been found in human IGFBP-3 and -4 (Rajaram et al 1997;Firth and Baxter 1999) and did not affect IGF binding, but probably could prolong the half-life of IGFBP in the circulation and promote its interaction with the cell surface Baxter 1999, 2002;Miller et al 2009). In fish IGFBP-2, because of lack of HBD, whether the N-glycosylated IGFBP-2 can bind to proteoglycans to associate with the cell surface or the extracellular matrix, and thus plays IGF-independent action needs more evidences and further reassessments.…”
Section: Discussionmentioning
confidence: 97%